2018
DOI: 10.1007/s11242-018-0999-0
|View full text |Cite
|
Sign up to set email alerts
|

Continuum-Scale Modeling of Liquid Redistribution in a Stack of Thin Hydrophilic Fibrous Layers

Abstract: Macroscale three-dimensional modeling of fluid flow in a thin porous layer under unsaturated conditions is a challenging task. One major issue is that such layers do not satisfy the representative elementary volume length-scale requirement. Recently, a new approach, called reduced continua model (RCM), has been developed to describe multiphase fluid flow in a stack of thin porous layers. In that approach, flow equations are formulated in terms of thickness-averaged variables and properties. In this work, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…This leads to the conclusion that a smaller total amount of PTFE can lead to the same transport characteristics of liquid water through the GDL micro-structure if it is located in the proper regions of the GDL. This result is consistent with the experiments of Tavangarrad et al (2018), who found that liquid water emerging from a hydrophobic layer of porous material does not tend to redistribute very much when it enters a hydrophilic region. Mortazavi and Tajiri (2013) measured contact angles on the surface of Toray GDL.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This leads to the conclusion that a smaller total amount of PTFE can lead to the same transport characteristics of liquid water through the GDL micro-structure if it is located in the proper regions of the GDL. This result is consistent with the experiments of Tavangarrad et al (2018), who found that liquid water emerging from a hydrophobic layer of porous material does not tend to redistribute very much when it enters a hydrophilic region. Mortazavi and Tajiri (2013) measured contact angles on the surface of Toray GDL.…”
Section: Resultssupporting
confidence: 93%
“…Shakerinejad et al (2018) studied GDL performance with the presence of hydrophilic layers inside, using the LB method for their simulations. Tavangarrad et al (2018) experimentally investigated the redistribution of PTFE in a situation where two thin layers of different hydrophobicity were stacked upon each other. Ito et al (2016) applied PTFE to Toray 090 GDLs using different techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lack of length scale separation characterizing the GDLs leads to question the relevance of the classical continuum approach to porous media in the case of GDLs, i.e. [31,32]. Combined with the fact that PNM computations are quite faster than LBM and easy to develop, this has led to the situation that PNM is nowadays the most popular numerical technique to study the https://doi.org/10.1016/j.ijheatmasstransfer.2018.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there are several challenges when measuring the unsaturated hydraulic properties of such thin layers. A layer is considered physically thin when the number of pores along its thickness is less than approximately 15 [see Qin and Hassanizadeh,7,8 Ceballos et al, 9 and Tavangarrad et al 10 ], with the thickness of a thin porous layer obviously being much smaller than its planar extent.…”
mentioning
confidence: 99%
“…11 Some measurements have been carried out also to determine the P c S ð Þ relationships of thin hydrophilic fabrics used in medical and hygienic absorbent products. 10,20,21 Several modeling studies also exist to estimate the capillary pressure-saturation curves of thin fibrous layers. For example, in a recent study, general expressions for the P c S ð Þ relationship of thin fabrics were developed for a family of fibrous media using a pore morphology methodology.…”
mentioning
confidence: 99%